Synergy of Central and Regional Government Policies to Entrepreneurs to Revive the National Economy in the New Normal Era - Dyah Ochtorina Susanti; Siti Nur Shoimah (Warmadewa Press, 2020)
This research is motivated by the phenomenan of Covid-19 pandemic has resulted in a decline in business income, but the implementation of the new normal policy revives a hope, so that in this case the policy efforts of the central and regional governments to revive the national economy in this new normal era is very needed. The purpose of this study is to analyse the synergy between central and regional government policies to entrepreneurs to revive the national economy in the new normal era. The study was designed in normative legal research with the statute approach, and conceptual approach. As a result showed that in the synergy of the central and regional government policies with entrepreneurs to revive the national economy in the new normal era, was realized through the providing Covid-19 impact stimulus, pouring out market operations, activating food houses, involving entrepreneurs in various Regional government spending, and providing economic stimulus for businessman.